Pemberian Ekstrak Etanol Akar Purwoceng pada Tikus Bunting Selama Masa Organogenesis Memperpanjang Ukuran Tulang Anak Tikus (ADMINISTRATION ROOTS ETHANOL EXTRACT OF PAMPINELLA ALPINA TO PREGNANT RATS DURING ORGANOGENESIS EXTENDS THE BONE OF THEIR PUPS) - Satyaningtijas, Aryani Sismin; Achmadi, Pudji; Maheshwari, Hera; Bustaman, Isdoni; Rahman, Dirwan; Zhaahir, Muhammad (Jurnal Veteriner; Vol 17 No 2 (2016), 2016)
Pregnancy is an integral part of the circulatory system between pups and mother. Growth anddevelopment of pups is determined by intake from their mother. The purpose of this study was to measurethe growth of pup’s bones given ethanol extract purwoceng (Pampinella alpine) for 1 to 13 days of ratgestation. Eight pregnant rats were divided into two groups: control group and purwoceng group that wasgiven ethanol extract purwoceng at a dose of 25 mg/300 g bw. The born pups were observed for 70 days tomeasure the growth and development of head bone, back bone, front legs bone, and hind legs. The resultsshowed that the growth and development of all bones parameters of female pups were higher on purwocenggroup than control the bone while male pups did not difference between purwoceng and control group exceptback bone and hind leg bone. The conclusion of this study is that administration of purwoceng roots ethanolextract on pregnant rats during organogenesis phase can extends the bone length of their pups.
Keywords: purwoceng (Pampinella alpine), roots ethanol extract, rats, bones